Nucleophilic Additions to Coordinated 1, 10‐Phenanthroline: Intramolecular, Intermolecular, Reversible, and Irreversible. Issue 50 (31st October 2016) - Arévalo, Rebeca; Menéndez, M. Isabel; López, Ramón; Merino, Isabel; Riera, Lucía; Pérez, Julio
Abstract: KN(SiMe3 )2 reacts with [Re(CO)3 (phen)(PMe3 )]OTf via reversible addition to the phen ligand and irreversible deprotonation of the PMe3 ligand followed by intramolecular attack to phen by the deprotonated phosphane, whereas MeLi irreversibly adds to phen. The addition of MeLi has been shown to be intermolecular, unlike previously known nucleophilic additions to pyridines. Abstract : An excellent electrophile : Coordinated 1, 10‐phenanthroline (phen) is usually considered a very inert ligand. However, phen in [Re(phen)(CO)3 (PMe)3 ]OTf (1 ) undergoes the nucleophilic addition of internal (the deprotonated trimethylphosphane ligand (2 )) and external (KN(SiMe3 )2 (3 M, 3 m ) and MeLi (4 M ‐C2 )) nucleophiles under mild conditions.